The Legal Analysis of Notary/PPAT Who Takes a Leave but Keep Make Legal Deed - Dinnie Angraeni; Nurfaidah Said; Hasbir Paserangi; Muhammad Ilham Arisaputra (Universitas Ahmad Dahlan, 2018)
Notary and Land Registrar (i.e. Pejabat Pembuat Akta Tanah [PPAT]) are general officials authorized to make authentic deeds. If someone is serving as a notary as well as being able to carry out his position, then he must be replaced by someone else temporarily. During the leave period, the land certificate they make is not authentic. The certificate sourced from and made by Notary or PPAT Deed is an authentic one that has perfect verification power. Therefore, every Notary or PPAT in carrying out the position should always be careful and aware of the consequences that can be caused on each deed he makes.